The Manila, the grand dame a survey of history and design - Tuason, Mary Joy J.; Mayo, Adelaida Villaraza (1994.)
The thesis study has sought to document the lifetime of the Manila Hotel, in a manner that is concise and more logically structured. This ensures understandability and ease in reading. The terms that have been exclusively used have been earlier define to prevent misinterpretations and vagueness. The study was undertaken following a rigorous order of methods that have been listed in the methodology. I researched in the Manila Hotel Archives for photos and other reference material regarding its history and design...
Research paper (ID 199)--University of the Philippines Diliman
Keywords: Manila Hotel -- Philippines -- History; Manila Hotel -- Philippines -- Interior decoration; Hotels -- Philippines